Contracts and uncertainty - Alvaro Sandroni; Wojciech Olszewski (Theoretical Economics, 2007)
A decision maker, named Alice, wants to know if an expert has significant information about payoff-relevant probabilities of future events. The expert, named Bob, either knows this probability almost perfectly or knows nothing about it. Hence, both Alice and the uninformed expert face uncertainty: they do not know the payoff-relevant probability. Alice offers a contract to Bob. If he accepts this contract then he must announce the probability distribution before any data are observed. Once the data unfold, transfers between Alice and Bob occur. It is demonstrated that if the informed expert accepts some contract then the uninformed expert also accepts this contract. Hence, Alice's adverse selection problem cannot be mitigated by screening contracts that separate informed from uninformed experts. This result stands in contrast with the analysis of contracts under risk, where separation is often feasible.
Keywords: C44; C73; D81; D83; D86; 330; Contracts; uncertainty; experts; minmax theorems